Os impactos financeiros em empresas brasileiras de e-commerce após o fim do isolamento social - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The e-commerce sector is increasingly one of the most common forms of consumption in Brazil and worldwide. E-commerce was propelled by the social isolation caused by Covid-19 and the change in consumption habits of the population during this period. In this context, this study aims to analyze the financial impacts after the end of social isolation on Brazilian e-commerce companies listed on the Brasil, Bolsa, Balcão. To this end, 25 companies were analyzed, and accounting and market indicators were evaluated between March 2018 and March 2022. The data were collected through the Economática® database, and descriptive analyses were conducted. The results indicate that the end of social isolation had a negative impact on the companies and showed a period of decline in the observed indicators. The practical implication of this result serves as a warning about fluctuations caused by atypical periods and allows companies, armed with the results, to guide strategies sustainably and allocate financial efforts according to market behaviors.
The financial impact on brazilian e-commerce companies after the end of social isolation
El impacto financiero en las empresas brasileñas de e-commerce tras del fin del aislamiento social
Keywords: E-commerce; Comércio eletrônico; Covid-19; Isolamento social; Indicadores financeiros; Social isolation; Financial indicators; Aislamiento social; CNPQ::CIENCIAS SOCIAIS APLICADAS